2013
DOI: 10.1007/s40292-013-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hypertension History on Short and Long-Term Prognosis in Patients with Acute Myocardial Infarction Treated with Percutaneous Angioplasty: Comparison Between STEMI and NSTEMI

Abstract: Previous studies analyzing the impact of hypertension (HTN) on myocardial infarction (MI) outcome reached conflicting results and scarce data are available in patients treated with percutaneous coronary intervention (PCI). In this study the prognostic impact of HTN history in ST-elevation MI (STEMI) and Non-STEMI (NSTEMI) patients treated with PCI was analyzed. We compared characteristics of 1,031 STEMI and 437 NSTEMI patients, in relation to the presence of HTN. Median follow-up duration was 40.2 months. HTN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…Lazzeri et al 36 assessed the influence of hypertension on the short-term and long-term outcome in 560 patients with STEMI submitted to mechanical revascularisation and found that a history of hypertension had no affect on either short-term or long-term mortality. Similar results were also found in Cecchi et al 's report 37. The reason why hypertension has no significant influence on the outcome in patients with STEMI who undergo PCI may be multifactorial.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lazzeri et al 36 assessed the influence of hypertension on the short-term and long-term outcome in 560 patients with STEMI submitted to mechanical revascularisation and found that a history of hypertension had no affect on either short-term or long-term mortality. Similar results were also found in Cecchi et al 's report 37. The reason why hypertension has no significant influence on the outcome in patients with STEMI who undergo PCI may be multifactorial.…”
Section: Discussionsupporting
confidence: 87%
“…One possible interpretation is that patients with hypertensive STEMI did not show a larger infarct size compared with normotensive patients, depicted by De Luca G et al 's study 38. Another possible explanation was the altered lifestyle and standard antihypertensive therapy after STEMI which controlled the main cardiovascular risk factors and resulted in a relatively fair outcome 37. However, although hypertension appeared to have no impact on the outcome in patients with STEMI who underwent PCI, patients with hypertension showed an altered glucose response to stress, as indicated by a higher incidence of acute insulin resistance and higher admission glucose values, which has been demonstrated to be a risk factor for 1-year mortality in patients with STEMI who underwent PCI with estimated glomerular filtration rate ≥60 mL/min/m 2 39.…”
Section: Discussionmentioning
confidence: 95%
“…Hypertension did not affect short-and long term mortality in patients with ST elevation myocardial infarction (STEMI) receiving PCI [2, 3]. However, hypertension was the only independent long-term predictor of mortality in patients with unstable angina (US) receiving coronary stenting [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cecchi et al studied the differential effect of hypertension on prognosis among 1031 patients with STEMI and 437 patients with NSTEMI treated with PCI. Hypertension was not associated with in‐hospital or long‐term mortality in either groups after adjustment for other risk factors . On the other hand, Abrigagni et al studied 4994 patients with MI and documented that hypertensive patients presented less frequently with cardiogenic shock, atrioventricular block, ventricular fibrillation, cardiac rupture, and ventricular thrombosis.…”
Section: Hypertension History In Patients With Acute Coronary Syndromesmentioning
confidence: 97%
“…Hypertension was not associated with in-hospital or long-term mortality in either groups after adjustment for other risk factors. 29 On the other hand, Abrigagni et al studied 4994…”
Section: Hyperten S I On His Tory In Patients With Acute Coronary Smentioning
confidence: 99%